2020
DOI: 10.25259/jcis_92_2020
|View full text |Cite
|
Sign up to set email alerts
|

Patients Radiation Risks from Computed Tomography Lymphography

Abstract: Objectives: This study aims to first measure patient doses during computed tomography (CT) chest, abdomen, and extremities procedures for evaluation lymphedema, and second to estimate the radiation dose-related risks during the procedures. Material and Methods: Radiation effective doses from CT lymphography procedures quantified using CT machines from different vendors. After the calibration of CT systems, the data collected for a total of 28 CT lymphography procedures. Effective and organ doses extrapolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…All five studies reported diagnostic test accuracies at different time points and with different thresholds. It is useful to view this study as an adjuvant to current clinical practice as CT scans expose patients to unrequired radiation exposure [52], particularly if patients have undergone radiological testing for AP recently. Studies with significant findings reported CRP cutoffs at 140 mg/L (p < 0.001) [46][47][48], 200 mg/L and 279 mg/L (p < 0.001) [49], and 98 ng/mL (p < 0.001) [51].…”
Section: Discussionmentioning
confidence: 99%
“…All five studies reported diagnostic test accuracies at different time points and with different thresholds. It is useful to view this study as an adjuvant to current clinical practice as CT scans expose patients to unrequired radiation exposure [52], particularly if patients have undergone radiological testing for AP recently. Studies with significant findings reported CRP cutoffs at 140 mg/L (p < 0.001) [46][47][48], 200 mg/L and 279 mg/L (p < 0.001) [49], and 98 ng/mL (p < 0.001) [51].…”
Section: Discussionmentioning
confidence: 99%